Foreign aid policies: Comparing Finland and Ireland - Elina Rissanen (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper is an analysis of the foreign Aid Policies of two OECD Development Assistance Committee member countries – Finland and Ireland. The analysis reveals that both Finland and Ireland share high principles on their relations with the developing world, although their current policy outlooks appear to differ significantly. Despite Finland's good economic performance and prosperity largely generated by the global demand and market access, the government has so far failed to include the increasing of ODA on its priority agenda. In addition to the declining commitment, the selection criteria for Finnish aid recipients appears to be partially commercially motivated. Ireland on the other hand has a solid record of targeting the poorest of the poor with its development assistance and has recently increased development country focus in national policies. The challenge for Ireland is the effective utilisation of these funds and even more importantly keeping the government's public, international commitment to the 0,7 percent recommendation level despite the possible future slowdown of the economy.
Keywords: 330; Official Development Assistance (ODA); Globalisation; Level of Integration; Trade; Entwicklungshilfe; Vergleich; Finnland; Irland